Racial, Religious, and Civic Dimensions of Anti-Muslim Sentiment in America. (17th October 2019) - Gerteis, Joseph; Hartmann, Douglas; Edgell, Penny
Abstract: This paper examines anti-Muslim sentiment in America. Existing research has documented rising hostility to Muslims in Western countries, but has been much less clear about what drives such sentiments or exactly what sort of "other" Muslims are understood to be. Our interest is in the cultural construction of Muslims as a problematic or incompatible "other." We explore the extent, content, and correlates of such views. Building from recent work in critical race theory and the study of cultural boundaries in national belonging, we argue that Muslims are distinct in being culturally excluded on religious, racial, and civic grounds at the same time. Using nationally representative survey data with specially designed measures on views of Muslims and other groups, we show that nearly half of Americans embrace some form of anti-Muslim sentiment, and that such views are systematically correlated with social location and with understandings of the nature of American belonging.